Measuring agility in software development teams: development and initial validation of the Agile Team Practice Inventory for Software Development (ATPI-SD) - Retzlaff, Niklas; Spörrle, Matthias (Frontiers in Computer Science, 2025)
IntroductionAgile methodologies are ubiquitous in software development, yet their measurement remains challenging due to a lack of validated instruments. This paper details the development and initial validation of the Agile Team Practice Inventory for Software Development (ATPI-SD), a new questionnaire measuring team-level agility based on core agile values and practices.MethodsStarting from a comprehensive literature review (258 items) and expert consultations (n = 7), five dimensions were initially identified, leading to 67 generated items. Expert feedback refined this to 37 items across 4 dimensions, which were tested in Study 1 (n = 199). Further analysis resulted in a final 20-item scale with four dimensions: Customer Involvement (CI), Team Collaboration (TC), Iterative and Incremental Development Processes (IIDP), and Continuous Development Process Improvement (CDPI).ResultsData from our study (n = 237) showed good internal consistency for the total scale (α = 0.89) and subscales (ranging from 0.69 to 0.84). Confirmatory Factor Analysis indicated a moderate-to-acceptable model fit (e.g., CFI = 0.88, TLI = 0.86). Moderate convergent validity was supported by a significant correlation with a single-item self-rating of team agility (p = 0.404, p < 0.001).DiscussionWhile suggesting potential for refinement, the ATPI-SD provides a systematically developed and initially validated instrument for researchers and practitioners assessing agility in software development teams.